Interactive strategy on patient safety: Experience report (Research, Society and Development, 2026)
Objective: To describe the implementation of an interactive activity open to the public developed by nursing residents about the Six International Patient Safety Goals in a Federal Hospital in Rio de Janeiro and the perceptions generated after its application. Methodology: A scenario was set up in the hospital hall with a mannequin presenting intentional nonconformities. Participants were invited to identify the errors present in the scenario, and at the end immediate feedback was provided, which promoted a discussion encouraging active learning. Results and discussion: Various professional categories, patients and companions participated in the activity. Significant engagement and feedback expanded knowledge about the importance of good multidisciplinary practices and raised participants' awareness of patient safety in the care environment. Conclusion: The educational strategy proved effective in promoting shared responsibility and strengthening the safety culture. Although simple, it has a positive impact on professional practice and generated an institutional proposal for the future development of a structured activity with a checklist focused on professionals.